2020
DOI: 10.30886/estima.v18.849_in
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of pressure injury and nursing care time in intensive care

Abstract: Objectives: To correlate the incidence of pressure injury (PI) with the average time of nursing care in an intensive care unit (ICU). Method: Epidemiological, observational, retrospective study, carried out in the ICU of a university hospital. Data were collected by consulting the PI incidence and the average nursing care time from ICU databases between 2010 and 2014. Measures of central tendency and variability, and Pearson’s correlation coefficient were used for data analysis. Results: The average incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, patients with an intensive care stay of less than 24 hours were excluded. Similarly, a Brazilian study of pressure injury in intensive care between the years 2010 and 2014 reported a mean pressure injury incidence of 10.8% (Ali et al, 2020) but pressure injury categories were not reported, and it is unclear whether Stage I injuries were included. In another Brazilian study, a notably higher incidence of 20.0% was reported in a small sample ( n = 40) (Rodrigues et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, patients with an intensive care stay of less than 24 hours were excluded. Similarly, a Brazilian study of pressure injury in intensive care between the years 2010 and 2014 reported a mean pressure injury incidence of 10.8% (Ali et al, 2020) but pressure injury categories were not reported, and it is unclear whether Stage I injuries were included. In another Brazilian study, a notably higher incidence of 20.0% was reported in a small sample ( n = 40) (Rodrigues et al, 2021).…”
Section: Introductionmentioning
confidence: 99%